Interferon Alpha-2a Treatment for Post-Uveitic Refractory Macular Edema. (17th February 2020) - De Simone, L.; Sangiovanni, A.; Aldigeri, R.; Mastrofilippo, V.; Bolletta, E.; Invernizzi, A.; Fares, L.; Pipitone, N.; Fontana, L.; Salvarani, C.; Cimino, L.
ABSTRACT: Purpose : To assess the efficacy of interferon (IFN) alpha-2a in the treatment of post-uveitic refractory macular edema (ME). Methods : Retrospective cohort of patients with post-uveitic refractory ME, who received subcutaneous IFN alpha-2a injections for at least 3 months. Baseline central macular thickness (CMT) and best-corrected visual acuity (BCVA) were compared with those at follow-up visits up to 12 months. Results : Thirty-seven patients were included. Treatment duration (median [interquartile range]) was 14[8–24] months with a follow-up of 17[10–38] months. CMT (mean [standard deviation]) decreased from 438[140] to 335[119] μm after 1 month (p < 0.0001) and remained significantly lower up to 12 months (286[98] μm, p = 0.001). BCVA (0.48[0.33] logMAR at baseline) improved by 0.26[0.33] logMAR (p = 0.001) at 12 months. There were 14 recurrences. Seven patients had treatment side effects, without serious adverse events. Conclusions : IFN alpha-2a was effective, safe, and well tolerated in treating post-uveitic refractory ME.